2014
DOI: 10.13063/2327-9214.1100
|View full text |Cite
|
Sign up to set email alerts
|

The Utah Beacon Experience: Integrating Quality Improvement, Health Information Technology, and Practice Facilitation to Improve Diabetes Outcomes in Small Healthcare Facilities

Abstract: Purpose:The Utah Improving Care through Connectivity and Collaboration (IC3) Beacon community (2010–2013) was spearheaded by HealthInsight, a nonprofit, community-based organization. One of the main objectives of IC3 was to improve health care provided to patients with diabetes in three Utah counties, collaborating with 21 independent smaller clinics and two large health care enterprises. This paper will focus on the use of health information technology (HIT) and practice facilitation to develop and implement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…For example, in a prior federally funded practice facilitation initiative, stakeholders determined that reliable and useful measures of diabetes performance were not available in practices' EHRs, which led them to develop a customized software system to promote QI work. 6 In addition, the quantitative results observed here reflect published qualitative findings from the national EvidenceNOW Initiative, 11 in which members of seven regional EvidenceNOW cooperatives (including the H3 trial conducted by our study team) reported challenges obtaining clinical quality reports from EHRs with time lines that aligned with QI project time lines. 14 Including one EHR vendor that created customized reports with rolling 12-month reporting periods only upon request, the majority of practices under study here (58/107; 54.2%) used an EHR without built-in features to produce quality measures with rolling 12-month reporting periods ( Table 2 ; rows H-K).…”
Section: Discussionsupporting
confidence: 79%
“…For example, in a prior federally funded practice facilitation initiative, stakeholders determined that reliable and useful measures of diabetes performance were not available in practices' EHRs, which led them to develop a customized software system to promote QI work. 6 In addition, the quantitative results observed here reflect published qualitative findings from the national EvidenceNOW Initiative, 11 in which members of seven regional EvidenceNOW cooperatives (including the H3 trial conducted by our study team) reported challenges obtaining clinical quality reports from EHRs with time lines that aligned with QI project time lines. 14 Including one EHR vendor that created customized reports with rolling 12-month reporting periods only upon request, the majority of practices under study here (58/107; 54.2%) used an EHR without built-in features to produce quality measures with rolling 12-month reporting periods ( Table 2 ; rows H-K).…”
Section: Discussionsupporting
confidence: 79%
“… Deployment and Intervention: Three of the submissions discuss the implementation challenges of HIT interventions within a community, such as incorporating HIE notifications in care coordination. 14 , 15 , 16 These papers have faced both technical and policy challenges in increasing the diversity of their stake-holders. Evaluation: A third of the articles focus on the evaluation of HIT-enabled, community-based transformations.…”
Section: The Current State Of the Artmentioning
confidence: 99%
“…2535 Little is known about how Facilitators respond to practice-level EHR data challenges that create barriers to performing data-driven QI. 18, 35, 36…”
Section: Introductionmentioning
confidence: 99%